2020
DOI: 10.3390/s20061738
|View full text |Cite
|
Sign up to set email alerts
|

Compensation Method for Sensor Network Clock Error Based on Cyclic Symmetry Algorithm

Abstract: Since the existing methods cannot evaluate the time delay of different layers of sensor networks, there are some problems such as the low precision of clock error compensation, high time delay, and low efficiency of communication in sensor networks. To solve this problem, a method of clock error compensation in sensor networks based on a cyclic symmetry algorithm is proposed. Based on the basic theory of cyclic symmetry, the cyclic symmetry matrix of the sensor network is constructed; in the communication proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These instruments inherently have different sources and magnitudes of errors due to different designs and operating principles. A previous study by [ 15 ] showed that many sensors and transducers were affected by the drift voltage because of the length wiring that caused voltage loss due to the increase in wire resistance. Other factors include loose wire connection and environmental factors such as the wire’s direct exposure to the sun and radioactivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These instruments inherently have different sources and magnitudes of errors due to different designs and operating principles. A previous study by [ 15 ] showed that many sensors and transducers were affected by the drift voltage because of the length wiring that caused voltage loss due to the increase in wire resistance. Other factors include loose wire connection and environmental factors such as the wire’s direct exposure to the sun and radioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…A compensation technique is needed to improve sensor accuracy measurement by eliminating the sensor error measurement. This technique enhances the persistence of power PV generation forecasting [ 15 , 16 ]. To the author’s best knowledge, previous studies on sensor error compensation have only focused on a single type of sensor.…”
Section: Introductionmentioning
confidence: 99%
“…The first paper presents a method of clock error compensation in sensor networks in order to provide a reference time for a wireless sensor network, which comprises the basis for real-time interaction, collaborative processing of sensor node information, and scheduling of network time [1]. The proposed method is based on a cyclic symmetry algorithm to compensate for the cumulative error of clock synchronization in the sensor network.…”
Section: Submissions Review Process Summary Of Contributionsmentioning
confidence: 99%